ANALISA USAHA PENYULINGAN MINYAK DAUN CENGKEH (Syzygium aromaticum, syn. Eugenia aromaticum) (Studi Kasus di Kecamatan Sukorejo Kabupaten Kendal) - Arif Khozali; Suprapti Supardi; Dewi Hastuti (Universitas Wahid Hasyim, 2012)
The purpose of research is to analyze the costs, revenues, income, level of feasibility in terms of BEP Gross B / C on clove leaf oil distillation business in the sub-District Kendal Sukorejo. The methodology used is a case study in the sub-District Kendal Sukorejo. The number of respondents 29 are all entrepreneurs who are distillation in sub-District Kendal Sukorejo, scattered in the village Puwosari, Ngargosari, Pesaren, Tamanrejo, Harjodowo, Damarjati, Mulyosari, Selokaton, Ngadiwarno and Kalibogor. The data used are primary and secondary data. The results showed that in the dry season the average cost incurred for clove leaf oil distillation business in a single distillation process of Rp 1,433,003,-/ distillation unit. The average revenue of Rp 1,615,586,-, so that during the dry season earned income of Rp 182,583,-. Value BEP production quantities clove leaf oil distillation at 16.21 kg and BEP rupiah at Rp 78,392,-/Kg, gross B/C ratio of 1.13 so that the business is feasible. While the rainy season the average cost incurred for clove leaf oil distillation business in a single distillation process of Rp 684,556,- / distillation unit. The average revenue of Rp 646,058,-, so that during the rainy season loss of Rp 38,498,-. Value BEP production quantities clove leaf oil distillation at 7.75 Kg and BEP rupiah at Rp 93,264,-/Kg, gross B/C ratio of 0.94 so that the business is not feasible in the rainy season. The conclusion of this research hypotheses 1 and 2 can be accepted, hypothesis 3 can be accepted during the dry season and the rainy season the hypothesis is rejected. Keywords: Clove Leaf Oil, Cost, Revenue, Income, BEP, Gross B/C Ratio